(untitled) (Canadian Oncology Today, 2024)
Colorectal cancer (CRC) is the third most diagnosed cancer in Canada and worldwide. Although mortality rates have declined, it remains the second most lethal malignancy worldwide. For patients with locally advanced rectal cancer (LARC), several new concepts have been introduced in recent years for treatment sequencing and de-escalation. The use of pelvic magnetic resonance imaging (MRI) for initial staging and neoadjuvant therapy response assessment has become a key part of the workup for LARC, utilizing the expertise of specialist radiologists. High-volume rectal cancer centers have adopted total neoadjuvant therapy (TNT) as a preferred approach for many patients with LARC. There is rising interest in shortening the duration of chemotherapy or radiation, or even omitting radiation altogether for select patients, to reduce the burden of long-term toxicities. For patients who achieve clinical complete or near-complete responses (cCR or nCR) to neoadjuvant therapies, nonoperative management (NOM) has emerged as an option to avoid the complications of a total mesorectal excision (TME). This paradigm shift has resulted in numerous treatment options for many patients with rectal cancer, enabling a more individualized, multidisciplinary approach to care. Clinicians must understand how to interpret the evidence around these new concepts to successfully implement them into clinical practice. This review summarizes the recent evidence for neoadjuvant therapy approaches in rectal cancer to provide a context for this paradigm shift to a tailored therapeutic strategy.